1993
DOI: 10.1042/bj2890117
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-operated Ca2+ channels in gastric parietal cells: gastrin and carbachol induce Ca2+ influx in depleting intracellular Ca2+ stores

Abstract: The mechanism whereby gastrin-type receptor and muscarinic M3-type receptor regulate free intracellular Ca2+ concentration ([Ca2+]i) was studied in rabbit gastric parietal cells stimulated by either gastrin or carbachol. Both agonists induced a biphasic [Ca2+]i response: a transient [Ca2+]i rise, followed by a sustained steady state depending on extracellular Ca2+. Gastrin and carbachol also caused a rapid and transient increase in Mn2+ influx (a tracer for bivalent-cation entry). Pre-stimulation of cells with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 47 publications
2
6
0
Order By: Relevance
“…Our results are in good agreement with the previously formulated concept of GR localization in the stomach (Roche et al 1991(Roche et al , 1993Kopin et al 1992;Chiba et al 1989;Soll and Walsh 1979;Soll et al 1984;Sutliff et al 1990;Delvalle et al 1993). The presence of the same receptor in chief and parietal cells is not surprising, because these cells are derived from the same stem cell during cellular differentiation in the isthmus of the gastric gland (Gordon 1993).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are in good agreement with the previously formulated concept of GR localization in the stomach (Roche et al 1991(Roche et al , 1993Kopin et al 1992;Chiba et al 1989;Soll and Walsh 1979;Soll et al 1984;Sutliff et al 1990;Delvalle et al 1993). The presence of the same receptor in chief and parietal cells is not surprising, because these cells are derived from the same stem cell during cellular differentiation in the isthmus of the gastric gland (Gordon 1993).…”
Section: Discussionsupporting
confidence: 93%
“…In addition to stimulation of secretion, gastrin increases the flow of blood to the mucosa, is involved in contraction of muscle, and has a trophic effect on the stomach, the duodenum, and the pancreas (for a review, see Mulholland and Debas 1988). Binding studies and investigations of diverse physiological effects of gastrin have demonstrated the presence of the hormone receptor on parietal cells (Roche et al 1993;Kopin et al 1992;Chiba et al 1989;Soll and Walsh 1979;Soll et al 1984), chief cells (Sutliff et al 1990), ECL-cells (Roche et al 1991), the D-cell (Delvalle et al 1993), and muscle cells (Grider and Makhlouf 1990) of the stomach. However, a recent study involving in situ hybridization techniques has failed to detect the gastrin/CCK B receptor (GR) on all these cell types and suggests that it is present, together with the histamine, muscarinic, and dopamine receptors, on immune cells in the lamina propria of the stomach (Mezey and Palkovits 1992), a conclusion that is hotly debated (Scott et al 1993;Shanahan and Anton 1993).…”
Section: Introductionmentioning
confidence: 98%
“…Gastrin is reported to be a growth‐promoting factor for cells that express gastrin receptors [1]. We and others have shown that parietal, ECL and D cells are specific cell types that have gastrin receptors on their cell membranes [3,13,14,17,18,21–24,27]. We have also shown that ECL cells with gastrin receptors proliferate when stimulated with gastrin [9,23].…”
Section: Discussionmentioning
confidence: 68%
“…PCNA‐positive cells had the same distribution pattern as those obtained by LCM. Gastrin receptor expression is evident in ECL, parietal and D cells [3,13,14,18,21–24,27], therefore, contamination by these cells in proliferating cells obtained by LCM may have been the major cause of the pseudopositive results for gastrin receptor gene expression seen in our experiments. Indeed, we found that only 32% of the LCM‐dissected samples were free from contamination by parietal, ECL or D cells.…”
Section: Discussionmentioning
confidence: 69%
“…The most important among these are stimulation of secretion in the stomach and growth-promoting effects on normal stomach and intestinal cells, as well as on gastrointestinal tumors. The consequences of gastrin binding to gastrin receptor-expressing cells include stimulation of cell growth [1,2], breakdown of phosphatidylinositol [3], mobilization of intracellular calcium [4,5] and activation of phospholipase C [6]. However, the mechanisms by which gastrin elicits its effects on cells are unclear.…”
Section: Introductionmentioning
confidence: 99%